“Squeezing Case(s)” with Melville: A Haptic Reading of “The Whiteness of the Whale” - Édouard Marsoin (Transatlantica)
This essay performs a haptic reading of “The Whiteness of the Whale” chapter in Melville’s Moby-Dick. Following Ishmael’s way of “squeezing cases” and touching upon epistemological issues, it explores how Melville’s fiction dramatizes the affective, epistemological, and literary capabilities of touch. Discussing previous work on hapticality in Melville and building upon recent developments regarding the role of the senses in close reading, it starts by delineating the synesthetic tendencies of Melville’s fiction, in which seeing and touching, the impalpable and the palpable, are intermingled in the quest of a “visible truth.” It then examines how, in “The Whiteness of the Whale,” the visual becomes palpable. Indeed, through a singular, underlying focus on textures, Ishmael’s discourse on whiteness performs a simultaneous, equally valid though contradictory alternative to what it says, and a haptic reading of it enables us to squeeze a sense of touch out of this intensely visual chapter. It also highlights the problematic racial implications of a category that erases differences and promotes a semblance of pure, abstract whiteness. Reading the chapter’s famous final paragraph as a painting enables us to recover the haptic phenomenological quality of colors through their textures, which unsettles traditional readings that equate whiteness with terrifying emptiness. A true epistemology of touch in Melville is therefore to be found in the reconfiguration of seeing as touching—what I call a process of becoming-synesthetic, which is revelatory of what literature can feel like—rather than in a mere reversal of the hierarchy between the two senses. Ultimately, this essay highlights the importance of synesthesia in the singular dynamics of literary discourse and its impact on our ways of reading.